Vmesni model za izvajanje plesne umetnosti v vrtcu - Geršak, Vesna (Revija za elementarno izobraževanje, 2012)
The article presents midway model with regard to introducing the art of dance in kindergarten by combining two poles, namely, the pedagogical (process) model on the one hand and the model of professional dance education on the other. The pedagogical model is based on the process as the most important element of dance creation. Commonly, the pedagogical model in practice mostly excludes the final product. The model of professional dance education, however, has objective goals and is focused on the product i.e. dance choreography which is in most cases preplanned and does not allow the participation of children. In this paper, the two models are linked to the results of a survey on dance education in Slovenian kindergartens and the findings based on working with students and pre-school teachers. Guidelines that combine the two opposing models, the pedagogical and the professional one, are presented herein and interpreted through their objectives and the implementation of the curriculum regarding dance education in kindergarten. We conclude that for quality employment of the art of dance in the preschool period, linking the two models is crucial, because it is the only way dance activities enable children to explore, re-experience things, express themselves, be creative, depict ideas as well as have an aesthetic experience and feel a glow of satisfaction on having completing the process and having presented their creation to others. In this way, the art of dance enables a child to develop on the cognitive, emotional, social, and psychomotoric level.
Keywords: dance; ples; didaktični model; teaching model; pre-school education; predšolska vzgoja; predšolski otroci; otroški vrtci; plesna umetnost